The six blind men and the elephant: Are episodic memory tasks tests of different things or different tests of the same thing? - Cheke, Lucy G. (J Exp Child Psychol, 2015)
The development of episodic memory in children has been of interest to researchers for more than a century. Current behavioral tests that have been developed to assess episodic memory differ substantially in their surface features. Therefore, it is possible that these tests are assessing different memory processes. In this study, 106 children aged 3 to 6 years were tested on four putative tests of episodic memory. Covariation in performance was investigated in order to address two conflicting hypotheses: (a) that the high level of difference between the tests will result in little covariation in performance despite their being designed to assess the same ability and (b) that the conceptual similarity of these tasks will lead to high levels of covariation despite surface differences. The results indicated a gradual improvement with age on all tests. Performances on many of the tests were related, but not after controlling for age. A principal component analysis found that a single principal component was able to satisfactorily fit the observed data. This principal component produced a marginally stronger correlation with age than any test alone. As such, it might be concluded that different tests of episodic memory are too different to be used in parallel. Nevertheless, if used together, these tests may offer a robust assessment of episodic memory as a complex multifaceted process.